Education Management towards Apparatus Ethics on Service Quality at the National Land Agency Office in Sidenreng Rappang Regency - Galuh Pujiawati; muhammad ikbal; Sapri Tajuddin (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the ethics of the apparatus towards the quality of service at the office of the National Land Agency of the Sidenreng Rappang Regency. This type of research is quantitative associative. This study uses two types of variables, namely variable X (ethics of personnel) and variable Y (quality of service). The results of this study from the results of processing the questionnaire obtained a variable recapitulation of service ethics of 65.5% in the "Good" category. Recapitulation of service quality variables of 60% is in the "Not Good" category. Recapitulation of indicators of factors that influence the service quality strategy by 60% is in the "Not Good" category, and the Influence between Service Ethics and Service Quality at the National Land Agency Office of Sidenreng Rappang Regency is categorized as "Influential/Significant",